Statistical analysis of sequence-structure alignment scores - Marcus Brunnert; Ralf Thiele; Heinz-Theodor Mevissen; Wolfgang Urfer (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2002)
The structural analysis of proteins is fundamental to the analysis of protein functions. In this context, sequence-structure alignment methods are important among the different empirical methods. In order to assess the quality of sequence-structure alignments, a statistical method using a Bayesian approach proposed by Lathrop et al. (1998) will be presented. Finally, the results of a developed statistical analysis of scores of RDP(recursive dynamic programming)-sequence-structure alignments (Thiele et al., 1999) according to data of six proteins will be described.
Keywords: 519; Sequence-structure-alignment; statistically significant scores; Combined Bayesian approach and RDP-alignment